Pengaruh model pembelajaran treffinger terhadap kemampuan berpikir kritis siswa pada mata pelajaran geografi - Ines Anugrah Bathari; Yuswanti Ariani Wirahayu (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2023)
Learning geography in the 21st century requires students to have critical thinking skills and can be trained through the Treffinger learning model. The Treffinger model invites students to think critically and creatively in every syntax. This study aims to determine the effect of the Treffinger learning model on students' critical thinking skills in geography subjects. This quasi-experimental study used the Post-test Only Control Group Design with the research subjects being students of class XI IPS 2 and XI IPS 3 of SMAN 1 Garum, Blitar Regency. The research instrument used was an essay test. Data analysis using the Independent Samples-Test obtained p-level data 0.03 less than 0.05 with a mean post-test score of the experimental class was 77, while the control class was 70. It was concluded that there was a significant influence of the Treffinger learning model on students' critical thinking skills in geography subjects. Pembelajaran geografi pada abad 21 menuntut siswa memiliki kemampuan berpikir kritis dan dapat dilatih melalui model pembelajaran Treffinger. Model Treffinger mengajak siswa berpikir kritis dan kreatif pada setiap sintaksnya. Penelitian ini bertujuan mengetahui pengaruh model pembelajaran Treffinger terhadap kemampuan berpikir kritis siswa pada mata pelajaran geografi. Penelitian eksperimen semu ini menggunakan desain Post test Only Control Group Design dengan subjek penelitian adalah siswa kelas XI IPS 2 dan XI IPS 3 SMAN 1 Garum, Kabupaten Blitar. Instrumen penelitian yang digunakan adalah tes essay. Analisis data menggunakan Independent Samples-Test memperoleh data p-level 0,03 kurang dari 0,05 dengan rerata nilai post-test kelas eksperimen adalah 77, sedangkan kelas kontrol adalah 70. Disimpulkan bahwa terdapat pengaruh yang signifikan model pembelajaran Treffinger terhadap kemampuan berpikir kritis siswa pada mata pelajaran geografi.